A study on ocular morbidities in children aged between 7 -18 years attending ophthalmology OPD - Ayesha Batool; Anand G. Gannur; Madhu A. Gannur; Z.A. Golewale; Zoha Arnib (Al Ameen Medical College, 2023)
Background: Ocular morbidities in children involve a spectrum of diseases that critically impact the development, education and quality of life hence require prompt attention. This study was conducted with an objective to assess the prevalence of ocular morbidity. Method: A hospital based cross- sectional study was carried out from November 2020 to April 2021 among children in age group between 7 to 18 years. Data was collected using a semi-structured questionnaire. Detailed eye examination was done under Slit lamp and visual acuity assessment was done using Snellen's chart. Children with vision less than 6/6p were subjected to refraction. Posterior segment evaluation was done under slit lamp with 90D and IDO. Results: A total of 120 children (7 to 18 years) were examined in this study. Majority of cases were between 14 to 18 years. 58.3% male and 41.6% female. Common presenting complaints were blurring of vision (28.3%) and headache (11.6%).The common ocular morbidity reported were refractive error (35.83%) followed by the allergic conjunctivitis (19.16%) and infections of the eye and adnexa (15.83%). Prevalence of refractive error was more in children aged between 14 to 18 years. Myopia was the most common refractive error. Conclusion: Most of the ocular morbidities are preventable or treatable. Ocular disorder can be easily identified with a regular eye screening. Moreover, health education for the prevention of ocular morbidity and early presentation to ophthalmology OPD for treatment is essential.